2011
DOI: 10.1002/ange.201100888
|View full text |Cite
|
Sign up to set email alerts
|

A Hypervalent Iodide‐Initiated Fragment Coupling Cascade of N‐Allylhydrazones

Abstract: Reliable bond-forming reactions that enable the union of two or more molecular fragments are essential for the efficient and convergent assembly of complex natural products or medicinal agents. [1] As part of a program aimed at developing such reactions, we have been investigating the utility of Nallylhydrazides as versatile chemical intermediates that allow for high yielding fragment coupling by way of hydrazone formation followed by a carbon-carbon bond-forming molecular rearrangement. [2] Most recently, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The reaction takes place via sequential three stages. After TMSOTf activates PhI(OAc) 2 to give PhI(OTf) 2 , [42][43][44][45] stage I generates an intermediate IM2 for the subsequent rearrangement process. The stage takes place by assembling PhI(OTf) 2 with E-3c to give EIM1, [46][47][48][49] followed by a MBH-like nucleophilic addition of 4-methylpyridine (denoted as Py) to an alkene carbon of EIM1.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction takes place via sequential three stages. After TMSOTf activates PhI(OAc) 2 to give PhI(OTf) 2 , [42][43][44][45] stage I generates an intermediate IM2 for the subsequent rearrangement process. The stage takes place by assembling PhI(OTf) 2 with E-3c to give EIM1, [46][47][48][49] followed by a MBH-like nucleophilic addition of 4-methylpyridine (denoted as Py) to an alkene carbon of EIM1.…”
Section: Resultsmentioning
confidence: 99%
“…In as ubsequentr eport, the Thomson group showed that the transformationc ould also occur by hypervalent iodine oxida-tion, whicha llowed fore ther formation insteado fc hloride incorporation (Scheme 6). [14] For example, the allyl hydrazone 23 could be formedf rom aldehyde 25 in situ and then treated with the oxidanti nt he presence of methanol. The hydrazone was oxidized to 35,w hich then rapidlyr earranged to the diazonium 36 in as imilarf ashion to the iminium 30.M ethanol could then nucleophilically displace dinitrogen to form 37.…”
Section: Sigmatropic Homoallylic Ether Formationmentioning
confidence: 99%
“…[3] The drawbacks of Pdand Cu-catalyzed N-arylation reactions include the requirement of high temperatures, long reaction times, the need for ligands and bases, and the generation of corrosive halide ions in many cases. Recently, Lutz and Thomson [7] reported a hypervalent iodine initiated fragment-coupling cascade reaction of N-allylhydrazones, conditions (base-free, -5°C) by using arylhydrazines as the arylating counterpart and arylamines. In the presence of copper salts, phenyllead triacetate [5] and triphenylbismuth [6] have found use in the synthesis of arylamines, but these reagents suffer from nonreactivity towards substrates containing electron-withdrawing substituents, and they are not ecofriendly, and, therefore, they are less popular.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of copper salts, phenyllead triacetate [5] and triphenylbismuth [6] have found use in the synthesis of arylamines, but these reagents suffer from nonreactivity towards substrates containing electron-withdrawing substituents, and they are not ecofriendly, and, therefore, they are less popular. Recently, Lutz and Thomson [7] reported a hypervalent iodine initiated fragment-coupling cascade reaction of N-allylhydrazones, conditions (base-free, -5°C) by using arylhydrazines as the arylating counterpart and arylamines. The scope of this method was demonstrated by using a number of arylhydrazines and arylamines, which gave the N-arylated amines in good yields.…”
Section: Introductionmentioning
confidence: 99%